Fatores motivacionais determinantes para prática de musculação e ginástica em adultos - OLIVEIRA, Arthur Cavalcante de (2019)
Physical exercise is one of the key components of a healthy lifestyle, and today the number of people looking for bodybuilding and gymnastics for such practices becomes quite expressive. By analogy with the principle of biological individuality we can understand that, however much they practice similar activities, different individuals tend to have different goals and motivations. Therefore, the main objective of this study is to analyze and compare the main motivational dimensions of adult men and women practicing regular bodybuilding and gymnastics. The sample consisted of 80 adult participants, divided into 40 men and 40 women, aged between 18 and 30 years who responded to the IMPRAF-54 instrument, which evaluates six dimensions of motivation, stress, health, sociability, competitiveness, aesthetics and pleasure. The results indicated that the most motivating dimension for the practice of bodybuilding and gymnastics was pleasure, followed by health and esthetics for both sexes. It was concluded that the main motivational factors for the practice of such modalities were the pleasure, health and esthetics, and also, that the female sex practices them for pleasure and aesthetics that the male sex, however, the is more competitive than the female sex.